Dancing with the populist: New parties, electoral rules and Italian municipal elections - Massimo Bordignon; Tommaso Colussi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2020)
This paper develops a theoretical framework that makes predictions on (a) the conditions under which a populist party decides to run and the policy position it takes and (b) voters' response under different electoral systems. We test these predictions using data on Italian municipal elections over the 2009-2019 period and focusing on the electoral outcomes of the Five Star Movement. The empirical analysis shows: (i) populists are more likely to run under a Dual Ballot (DB) system and in municipalities where there is a large share of dissatisfied voters; (ii) when the populist runs, turnout increases under both Single and Dual Ballot systems; (iii) in a DB system, the populist candidate who ranked second in the first round has a higher probability of winning than the candidate of traditional party who ranked second by the same margin, as a result of increased turnout in the second round. We finally provide evidence that the low education and the young age of populist candidates are likely to deteriorate the efficiency of the local administration.
Keywords: D72; D74; H56; D91; 330; Voting behavior; Populism; Five Star Movement; municipal elections